1999
DOI: 10.1159/000007692
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Increases Apoptosis in the Gastric Mucosa: Role of Epidermal Growth Factor

Abstract: Background/Aims: Apoptosis is a common mechanism for the regulation of cell loss. It is associated with both tissue atrophy and metaplasia. Cigarette smoking has tremendous adverse effects on the stomach and also increases the risk of gastric cancer. This action may be through the change in apoptosis in the stomach. The aim of this study was to examine the effect of cigarette smoking on apoptosis in the gastric mucosa and the possible role of epidermal growth factor (EGF) in this action. Methods: Gastric blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The most plausible explanation for these findings is that smoking causes cellular injury due to oxidative stress. [25][26][27] This is the first report that describes smoke-induced apoptosis in the intestine. It is Smoking alters intestinal apoptosis and GALT S Verschuere et al known that small erosions are found in the FAE of patients with CD.…”
Section: Discussionmentioning
confidence: 92%
“…The most plausible explanation for these findings is that smoking causes cellular injury due to oxidative stress. [25][26][27] This is the first report that describes smoke-induced apoptosis in the intestine. It is Smoking alters intestinal apoptosis and GALT S Verschuere et al known that small erosions are found in the FAE of patients with CD.…”
Section: Discussionmentioning
confidence: 92%
“…These cells were distributed in different regions across the gastric glandular mucosa [14]. The gastritis group had a higher number of apoptotic cells compared to the corresponding control (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, cigarette smoke exposure significantly decreased serum epidermal growth factor (EGF) levels (Ma et al, 1999). Although the mechanisms by which cigarette smoke exposure decreases serum EGF are still unknown, depletion of EGF has been associated with reduced gastric blood flow, which in turn, results in the promotion of apoptosis in the gastric mucosa (Ma et al, 1999;Wang et al, 2000). The contents of cigarette smoke may form DNA adducts and induce mutations in tumour suppressor genes (Shin and Cho, 2005).…”
Section: Discussionmentioning
confidence: 99%